2004
DOI: 10.1111/j.1365-2265.2004.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism is associated with a low‐grade inflammation, increased triglyceride levels and predicts cardiovascular disease in males below 50 years

Abstract: Our study demonstrates that patients with subclinical hypothyroidism have increased levels of triglycerides and signs of low-grade inflammation (raised C-reactive protein levels) and that subclinical hypothyroidism might be a risk factor for development of cardiovascular disease in younger males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
149
3
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(188 citation statements)
references
References 28 publications
26
149
3
10
Order By: Relevance
“…Other studies have also reported similar findings. [8][9][10]17,19 We also observed a higher prevalence of diastolic hypertension in hypothyroid patients (64.3%) compared to euthyroid patients (34.9%). Similar results were obtained in other studies also.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Other studies have also reported similar findings. [8][9][10]17,19 We also observed a higher prevalence of diastolic hypertension in hypothyroid patients (64.3%) compared to euthyroid patients (34.9%). Similar results were obtained in other studies also.…”
Section: Discussionsupporting
confidence: 54%
“…9,[12][13][14][15] Elevated homocysteine levels and low grade inflammation, as suggested by elevated CRP are the other risk factors for coronary artery disease in hypothyroidism. 16,17 This study was conducted to find out the prevalence of hypothyroidism in patients with coronary artery diseaseacute myocardial infarction and to find out the relation of hypothyroidism to factors like hypercholesterolemia and diastolic hypertension in the study population.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other studies have demonstrated that subclinical hypothyroidism represents an independent risk factor for coronary heart disease. [16][17][18] It has been suggested by Stabouli et al, 15 and we agree, that patients visiting a hypertension clinic for evaluation of high BP may benefit from the diagnosis of hypothyroidism as the majority of them would avoid antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, Cappola et al (2006), in a large population-based, longitudinal study of coronary heart disease and stroke in adults aged 65 years and older, concluded that the results did not support the hypothesis of an association between unrecognized sHT and increased CV events or mortality. On the other hand, one cross-sectional study with subgroup analyses by age found that increased risk for CHD was present in younger sHT participants only (<50 years old) (Kvetny et al 2004). In this regard, a prospective, observational, population-based follow-up study carried out on 599 participants followed up from age 85 years through age 89 years showed no association between serum TSH and FT4 levels and disability in daily life, depressive symptoms, and cognitive impairment at baseline or during follow-up.…”
Section: Clinical Evidencesmentioning
confidence: 99%
“…Comparable results were obtained after administration of celecoxib, a selective COX-2 inhibitor, thus suggesting that an association between thyroid function and lowgrade systemic inflammation could be postulated. Accordingly, several studies (Kvetny et al, 2004;Luboshitzky et al, 2004;Christ-crain et al, 2003;Lee et al, 2004) investigated the possible relationship between TH deficiency and serum CRP level, that was mostly found higher in hypothyroid patients, although unaffected by LT4 therapy (Christ-crain, 2003).…”
Section: Pathophysiologymentioning
confidence: 99%